2011
DOI: 10.1177/147323001103900634
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Repair Compared with Delayed Repair of Congenital Omphalocele: Short-Term Neonatal Outcomes in China

Abstract: This prospective study evaluated the short-term outcomes of 16 neonates undergoing single congenital omphalocele repair. Parents made informed choices for their baby to receive either immediate repair (IR group, n = 8) or repair ≥ 3 h after delivery (control group, n = 8). All babies were delivered by elective caesarian section. Babies in the two groups were matched one-to-one according to their birth weight, bulging volume and gestational age. Short-term outcomes included the incidence of infection and the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Acorroding an early study, it has been reported that patients with GO are less likely to undergo management with early closure compared with small omphalocele (12). In a study of omphalocele by Na et al (13), the immediate repair (IR group) was defined as undergoing surgery immediately after birth (usually less than 10 minutes), and after 3 hours of life, the surgical repair was defined as a late repair (control group). The children in the IR group started enteral nutrition earlier, had a lower infection rate, and had a shorter hospitalization time than those in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Acorroding an early study, it has been reported that patients with GO are less likely to undergo management with early closure compared with small omphalocele (12). In a study of omphalocele by Na et al (13), the immediate repair (IR group) was defined as undergoing surgery immediately after birth (usually less than 10 minutes), and after 3 hours of life, the surgical repair was defined as a late repair (control group). The children in the IR group started enteral nutrition earlier, had a lower infection rate, and had a shorter hospitalization time than those in the control group.…”
Section: Discussionmentioning
confidence: 99%